A Ligation of the Lacrimal Excretory Duct in Mouse Induces Lacrimal Gland Inflammation with Proliferative Cells - Liu, Ying (Stem Cells Int, 2017)
The lacrimal gland secretes tear fluids to ocular surface, which plays an indispensable role in maintaining the health of the ocular epithelia and protecting the ocular surface from the external environment. The dysfunction of the lacrimal glands causes dry eye disease due to a reduction in tear volume. The dry eye disease is becoming a popular public disease, for the number of patients is increasing, who have subjective symptom and loss of vision, which affect the quality of life. Inflammatory change in the damaged lacrimal gland has been reported; however, a major challenge is to establish a simple animal model to observe the changes. Here, we demonstrated an injury model by ligating the main excretory duct of the lacrimal gland, which is a simple and stable way to clearly understand the mechanism of lacrimal gland inflammation. We observed the process of injury and proliferation of the lacrimal gland and detected a population of lacrimal gland epithelial cells with proliferation potential which were also nestin-positive cells following duct ligation. This study successfully established an injury model to observe the tissue injury process of the lacrimal gland, and this model will be useful for analysis of the inflammation and proliferation mechanism in the future.